2022
DOI: 10.1039/d1ta10330j
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light photocatalytic hydrogen production in a narrow-bandgap semiconducting La/Ni-modified KNbO3 ferroelectric and further enhancement via high-field poling

Abstract: Compared with traditional wide-bandgap oxide ferroelectrics that exhibit excellent UV photocatalysis, narrow-bandgap semiconducting ferroelectrics demonstrate broad application prospects in the field of visible-light photocatalysis. However, due to the significant current...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 49 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…25,26 Li + substitution has been studied in depth to construct the O-T phase boundary. 27,28 Moreover, as a comprehensive and useful additive, the Mn ions in MnO 2 have different valence states (+2, +3, and +4). 7,12 On the other hand, the single crystal has leakage current on account of the presence of lattice defects.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Li + substitution has been studied in depth to construct the O-T phase boundary. 27,28 Moreover, as a comprehensive and useful additive, the Mn ions in MnO 2 have different valence states (+2, +3, and +4). 7,12 On the other hand, the single crystal has leakage current on account of the presence of lattice defects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the first exploration of the phase boundary of KNN-based ceramics in 2004, excellent piezoelectric properties have been continuously obtained in KNN with an O-T phase boundary. Various studies on the O-T phase boundary have accumulated rich experience on how to select effective potential additives for KNN. In general, the phase boundary in KNN crystals can be regarded as the intrinsic features of polymorphic phase transition (PPT), which can shift to room temperature by adjusting element doping. , Li + substitution has been studied in depth to construct the O-T phase boundary. , Moreover, as a comprehensive and useful additive, the Mn ions in MnO 2 have different valence states (+2, +3, and +4). , On the other hand, the single crystal has leakage current on account of the presence of lattice defects. , Low leakage current and the additional high antifatigue properties in Mn-doped KNN crystals were obtained in recent work . In the condition of KNN-LN doped with MnO 2 , Mn ions substitute A or B sites as electron or hole absorber during oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…However, KNbO 3 has a wide band gap (about 3.3 eV), which greatly limited the utilization of visible light and the efficiency of photocatalytic oxidation of NO. 15,16 It had been reported that the introduction of defects such as oxygen vacancies (OVs) can well solve the problem of low utilization of visible light by forming impurity energy levels. 17,18 Moreover, the existence of OVs was beneficial to the adsorption and activation of NO and O 2 , thereby improving the photocatalytic oxidation performance of NO.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on energy harvesting and energy conversion. Ferroelectric materials, which lack bulk inversion symmetry and have spontaneous polarizability, have many applications in fields such as piezoelectric transducers, 1,2 photovoltaic converters, 3,4 and photocatalysis 5–7 . Conventional photovoltaic devices imprisoned in the semiconductor energy band have a limited photogenerated voltage, 8 which is not sufficient for increasing the photovoltaic conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric materials, which lack bulk inversion symmetry and have spontaneous polarizability, have many applications in fields such as piezoelectric transducers, 1,2 photovoltaic converters, 3,4 and photocatalysis. [5][6][7] Conventional photovoltaic devices imprisoned in the semiconductor energy band have a limited photogenerated voltage, 8 which is not sufficient for increasing the photovoltaic conversion efficiency. Ferroelectric photovoltaic materials with both bulk photovoltaic effect 9 and electrostatic potential at the nano-domain wall, 10 which can generate photovoltaic voltages above the bandgap, can further improve the photovoltaic conversion efficiency and are potential candidates for next-generation photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%